The consequences of exchange rate fluctuations on Nigeria's economic performance: An autoregressive distributed lag (ARDL) approach - Nkemdilim Iheanachor; Azuka Elvis Ozegbe (International Journal of Management, Economics and Social Sciences (IJMESS), 2021)
This study examined the effects of persistent exchange rate fluctuations on Nigeria's economic performance. It was motivated by the quest to ascertain why concerted efforts of the monetary authorities in Nigeria to pursue internal and external balances yielded little or no positive results in recent periods. The study employed the autoregressive distribution lag (ARDL) technique to test the short-run and long-run effects of exchange rate fluctuations on economic growth using annual time series data from 1986 to 2019. The empirical result revealed that the exchange rate, net direct foreign direct investments, and inflation rate had a significant adverse impact on Nigeria's economic growth in the long run. By implication, the net effect of this study established that excessive exchange rate fluctuations are detrimental to Nigeria's economic growth. On the premise of the empirical findings, this study recommends export diversification in agriculture and agro-investment in Nigeria. The state should influence the foreign exchange system through credible reforms that would reduce the adverse effects of an unstable foreign exchange system on the Nigerian economy.
Keywords: C1; F4; F31; 330; Exchange rate fluctuations; monetary policy; economic growth; Nigeria; Autoregressive Distribution Lag (ARDL)